Evaluation of Antibacterial, Antifunfgal and Cytotoxic Potentials of Crude Metabolite of ANAM-39, a Marine Bacterium Isolated from Sundarbans, Bangladesh - Sarker, Ashish Kumar; Haque, Md Anwarul; Saha, Urmi; Rahman, Md Ajijur; Islam, Md Anwar Ul (Bangladesh Pharmaceutical Journal, 2015)
The present study was undertaken to screen the antimicrobial, antifungal and cytotoxic potentials of crude metabolite of a marine bacterium isolated from a soil sample collected from Sundarbans, Bangladesh. Primary and secondary screenings for antimicrobial activity were conducted by cross streak and agar well diffusion method, respectively. The antifungal potency of the crude extract was also tested by agar well-diffusion method. The brine shrimp lethality test was conducted to determine the cytotoxic nature of crude metabolites, which showed that the degree of lethality of metabolite was directly proportional to the concentration (LC50 30.19 ?g/ml). Further studies are needed to isolate and characterize the active principles present in the crude metabolite and determine their biological activity. The results of this investigation suggested that the soils of Sundarbans are rich sources of microorganisms with potent biological activities and systematic screening programs need to be conducted to explore the presence of pharmacologically active marine bacterial metabolites. Bangladesh Pharmaceutical Journal 18(2): 103-109, 2015